EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES THROUGH PAKEM LEARNING MODEL ON IPS IPS LESSONS IN CLASS V SDN 2 SINDUE - Midian Midian; Rizal Rizal (Education Journal, 2020)
The purpose of this study was to improve student learning outcomes in fifth grade. This study uses a Kemmis and Mc. Taggart which consists of two cycles. In each cycle two meetings were held. The results of the study, the pre-action percentage of classical absorption 48.26% and classical learning completeness 18.51%, the results of the first cycle research with 66.86% classical absorption and classical learning completeness 78.26%. Increased in the second cycle with the results of the percentage of classical absorption of 76.52% and classical learning completeness of 91.30%. The average activity of teacher and student activities in the research activities of teachers in the first cycle of 71.42%, meeting student activities 75% , increased in cycle II teacher activity 92.85%, and student activities 92.85%. Based on these results it can be concluded that by applying the PKEM learning model can improve student learning outcomes in social studies subjects in class V SDN 2 Sindue.